Increasing utilization of pediatric epilepsy surgery in the United States between 1997 and 2009. (29th January 2015) - Pestana Knight, Elia M.; Schiltz, Nicholas K.; Bakaki, Paul M.; Koroukian, Siran M.; Lhatoo, Samden D.; Kaiboriboon, Kitti
Summary: Objective: To examine national trends of pediatric epilepsy surgery usage in the United States between 1997 and 2009. Methods: We performed a serial cross‐sectional study of pediatric epilepsy surgery using triennial data from the Kids' Inpatient Database from 1997 to 2009. The rates of epilepsy surgery for lobectomies, partial lobectomies, and hemispherectomies in each study year were calculated based on the number of prevalent epilepsy cases in the corresponding year. The age‐race‐sex adjusted rates of surgeries were also estimated. Mann‐Kendall trend test was used to test for changes in the rates of surgeries over time. Multivariable regression analysis was also performed to estimate the effect of time, age, race, and sex on the annual incidence of epilepsy surgery. Results: The rates of pediatric epilepsy surgery increased significantly from 0.85 epilepsy surgeries per 1, 000 children with epilepsy in 1997 to 1.44 epilepsy surgeries per 1, 000 children with epilepsy in 2009. An increment in the rates of epilepsy surgeries was noted across all age groups, in boys and girls, all races, and all payer types. The rate of increase was lowest in blacks and in children with public insurance. The overall number of surgical cases for each study year was lower than 35% of children who were expected to have surgery, based on the estimates from the Connecticut Study of Epilepsy. Significance: In contrast to adults, pediatric epilepsy surgery numbers have increased significantly in the past decade. However, epilepsy surgery remains an underutilized treatment for children with epilepsy. In addition, black children and those with public insurance continue to face disparities in the receipt of epilepsy surgery.